Комплекс строительной керамики первых веков нашей эры из портового района Херсонеса - Магда, А. В.; Ильина, О. М. (Давнина. Харківський історико-археологічний щорічник, 2016)
Magda A. V., Illyina O. M. The Construction Ceramics Complex from the Times of I–IV Centuries in the in the Port-Side Section of Chersonessus